Money, so much money: Reading Tahel Frosh’s Avarice - Jacobs, A (Stanford University, 2018)
In this article, I address the work of the Israeli poet Tahel Frosh, whose debut collection Avarice (2014) advances a critical commentary on neoliberalism and the privatization of the Israeli economy. Against official accounts of Israel’s economic history and their emphasis on development and growth, Frosh’s poetry offers an accounting of the toll of capitalism and the free market on individual bodies and spaces. Her work also proposes an intersectional reading of gender, economy, and the value of poetic labor set against the backdrop of the 2011 social justice protests in Israel. Acknowledging the market relations between Israel and the United States, my reading brings Frosh’s work into relation with that of the U.S. poets Anne Boyer, Lorine Niedecker, and Laura Sims, highlighting points of comparison in the formal strategies that shape their critique of capital and labor.